175k views
0 votes

R = \sqrt{ (ax - P)/(Q + bx) }

solve for x. Please can someone help me ASAP. I need to hand it on today.​

2 Answers

2 votes

Answer:


\displaystyle x=\frac{-P-\math{R}^2Q}{\math{R}^2b-a}

Explanation:


R=\sqrt{(ax-P)/(Q+bx)}


\mathrm{Square\:both\:sides}


R^2=\left(\sqrt{(ax-P)/(Q+bx)}\right)^2


R^2=(ax-P)/(Q+bx)


\mathrm{Multiply\:both\:sides\:by\:}Q+bx


\math{R}^2\left(Q+bx\right)=(ax-P)/(Q+bx)\left(Q+bx\right)


\math{R}^2\left(Q+bx\right)=ax-P


\math{R}^2Q+\math{R}^2bx=ax-P


\mathrm{Subtract\:}\math{R}^2Q\mathrm{\:from\:both\:sides}


\math{R}^2Q+\math{R}^2bx-\math{R}^2Q=ax-P-\math{R}^2Q


\math{R}^2bx=ax-P-\math{R}^2Q


\mathrm{Subtract\:}ax\mathrm{\:from\:both\:sides}


\math{R}^2bx-ax=ax-P-\math{R}^2Q-ax


\math{R}^2bx-ax=-P-\math{R}^2Q


\mathrm{Factor}\:\math{R}^2bx-ax


x\left(\math{R}^2b-a\right)=-P-\math{R}^2Q


\mathrm{Divide\:both\:sides\:by\:}\math{R}^2b-a


\frac{x\left(\math{R}^2b-a\right)}{\math{R}^2b-a}=-\frac{P}{\math{R}^2b-a}-\frac{\math{R}^2Q}{\math{R}^2b-a}


x=\frac{-P-\math{R}^2Q}{\math{R}^2b-a}

User Bill Christo
by
5.5k points
3 votes

Explanation:


r = \sqrt{ (ax - p)/(q + bx) } \\ {r}^(2) = (ax - p)/(q + bx)

r² (q + bx) = ax - p

qr² + bxr² = ax - p

qr² + p = ax - bxr²

qr² + p = x (a - br²)


x = \frac{q {r}^(2) + p}{a - b {r}^(2) }

User Papa
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.